Pengaruh Kegiatan Seni Berbasis Budaya Lokal terhadap Kreativitas Anak Usia Dini di TK Sukma Nusa Bangsa - Siti Hairin M. Wawo; Elva M. Sumirat; Febri Wanda Tongka; Yuliana Asiking; Tantri Adam (Jurnal Pendidikan Anak Usia Dini dan Kewarganegaraan, 2026)
This study aims to determine the effect of local culture-based art activities on student creativity at Sukma Nusa Bangsa Kindergarten. Creativity is an important aspect of early childhood development because it supports children’s ability to think imaginatively, express ideas, solve problems, and develop self-confidence. This study employed a quantitative approach using a one-group pre-test post-test design. The research subjects consisted of 10 kindergarten students who participated in a series of local culture-based art activities. Data were collected through observation and documentation techniques, while data analysis was conducted using the Wilcoxon Matched Pairs Test to determine differences between pre-test and post-test scores. The results showed a significant improvement in student creativity after the implementation of the intervention. The average pre-test score of 58.6 increased to 79.4 on the post-test, indicating an improvement of 20.8 points. Furthermore, the Wilcoxon test yielded a significance value of p = 0.005, which is lower than 0.05, leading to the rejection of H0 and acceptance of H1. These findings indicate that local culture-based art activities effectively enhance students’ creativity, particularly in expressing ideas, utilizing imagination, and producing creative works. Therefore, integrating local cultural elements into learning activities can serve as an effective strategy for fostering creativity in early childhood education.